2013
DOI: 10.1080/21552851.2013.803758
|View full text |Cite
|
Sign up to set email alerts
|

The role of the state in the development of accounting in the Portuguese–Brazilian Empire, 1750–1822

Abstract: This paper explores the role of the state in the development of accounting in the Portuguese-Brazilian Empire (1750-1822) in the context of economic and political transformations. In this period, the interrelations of accounting and the state were central to understanding accounting change in Portugal and Brazil. Through control of accounting education, organization of the accounting occupation, rules of corporate governance and governmental accounting itself, governments adopted accounting technologies in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
0
22
0
4
Order By: Relevance
“…Previous studies have shown that accounting can be included within such mechanisms, demonstrating its strength to manage individuals and associations to achieve desired government objectives (Burchell et al, 1985;Miller and O'Leary, 1994;Preston et al, 1997;Radcliffe, 1999;Neu, 2000aNeu, , 2000bÁlvarez-Dardet et al, 2002;Jeacle and Walsh, 2002;Baños Sánchez-Matamoros et al, 2005;Sargiacomo, 2008Sargiacomo, , 2009Yayla, 2011;Rodrigues and Sangster, 2013). Sargiacomo (2008), in particular, has shown how the abovementioned approach can be fruitful in analysing the way of governing in Italian states in the second half of the sixteenth century, by examining the emergence of accounting, accountability and disciplinary practices in the feudal State of Abruzzo.…”
Section: Accounting Technologies Of Governmentmentioning
confidence: 99%
“…Previous studies have shown that accounting can be included within such mechanisms, demonstrating its strength to manage individuals and associations to achieve desired government objectives (Burchell et al, 1985;Miller and O'Leary, 1994;Preston et al, 1997;Radcliffe, 1999;Neu, 2000aNeu, , 2000bÁlvarez-Dardet et al, 2002;Jeacle and Walsh, 2002;Baños Sánchez-Matamoros et al, 2005;Sargiacomo, 2008Sargiacomo, , 2009Yayla, 2011;Rodrigues and Sangster, 2013). Sargiacomo (2008), in particular, has shown how the abovementioned approach can be fruitful in analysing the way of governing in Italian states in the second half of the sixteenth century, by examining the emergence of accounting, accountability and disciplinary practices in the feudal State of Abruzzo.…”
Section: Accounting Technologies Of Governmentmentioning
confidence: 99%
“…A revisitação do tema, além de fundamentar a pertinência da pesquisa, pode ajudar à criação de novas e diferentes motivações para a abordagem de um dos momentos-chave da evolução e institucionalização da profissão de contabilista em Portugal, por norma o primeiro a ser cronologicamente listado pela maioria dos autores (cf. Rodrigues e Gomes, 2002, p. 132;Matos, 2016, p. 25) que ao tópico dedicam as suas pesquisas; ─ depois, em quarto lugar, porque o paper consolida, em linha com os traços nele apresentados, uma ideia que é sabida, a de que "todas as profissões se baseiam em conhecimento específico que é construído nas instituições de ensino […] e difundido aos alunos (futuros profissionais) através do ensino" (Rodrigues, 2016a, p. 5); ─ e, por último, mas não menos importante, porque a contribuição permite dar continuidade a uma linha de investigação internacional muito profícua nos últimos cinco anos (Rodrigues, Schmidt, Santos e Fonseca, 2011;Rodrigues, Schmidt e Santos, 2012;Araújo, 2013;Rodrigues e Sangster, 2013;Araújo et al, 2016) acerca do processo de institucionalização das partidas dobradas no Brasil e do desenvolvimento da contabilidade nessa antiga colónia portuguesa, nomeadamente porque este artigo deu a conhecer, pela primeira vez na literatura, que o tesoureiro-mor do Erário Régio, organização estabelecida no Brasil em 1808, foi aluno da Aula do Comércio de Lisboa: Francisco Bento Targini (1756-1827) era o seu nome e ele foi aulista do 4.º curso (1771-1774) (Arquivo Nacional da Torre do Tombo, Junta do Comércio, Livro 328, fólio 6v). O lugar de tesoureiro-mor do Erário Régio, correspondia, depois do presidente da instituição, à mais alta função em exercício na organização que, depois da fuga da família real para o Brasil em 1807 como resposta à ocupação francesa em Portugal, o Príncipe D. João decidiu criar no Rio de Janeiro, à semelhança da existente em Lisboa desde 1761.…”
Section: Conclusãounclassified
“…Moreover, by the mid mid-eighteenth century, DEB had legitimacy among European merchants due to the various benefits that its adoption provided to mercantile enterprises (Rodrigues & Sangster, 2013). For this reason, the Diretório Econômico ( §XXIX) ordered the mandatory use of DEB for the PPC (Rodrigues & Sangster, 2013). …”
Section: The Accounting System Of the Ppcmentioning
confidence: 99%
“…Besides those, Pombal himself was also familiar with DEB (Oliveira, 2014;Rodrigues & Sangster, 2013). …”
Section: The Accounting Departmentmentioning
confidence: 99%
See 1 more Smart Citation